2006
DOI: 10.1007/s10620-006-9301-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Zinc Sulfate and Metallothionein in Protection Against Ethanol-Induced Gastric Damage in Rats

Abstract: In this study, the effects of zinc sulfate against ethanol-induced acute gastric damage in rats were investigated, morphologically and biochemically. In addition, the present investigation has demonstrated the distribution of metallothionein stimulated by zinc in gastric mucosal tissues, immunohistochemically. The gastric damage was induced by intragastric administration of 1 ml absolute ethanol per rat. Rats received zinc sulfate (100 mg/kg/day) for 3 consecutive days 2 hr prior to the administration of absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…They were sham (S) group: animals received normal saline (N/S; 2 mL Kg −1 ) [41] for 7 consecutive days, intraperitoneally (ip) [45]; then laparotomy without IR induction was performed. IR group: animals received N/S with the same dose and time; then IR induction was carried out as mentioned before.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were sham (S) group: animals received normal saline (N/S; 2 mL Kg −1 ) [41] for 7 consecutive days, intraperitoneally (ip) [45]; then laparotomy without IR induction was performed. IR group: animals received N/S with the same dose and time; then IR induction was carried out as mentioned before.…”
Section: Methodsmentioning
confidence: 99%
“…Crocin is a water soluble carotenoid and the most important active constituent of saffron [39]. Crocin, as an antiapoptotic, anti-inflammatory, and antioxidant agent [40], has many beneficial protective effects against renal [41], gastric [42], retinal [43], and brain [44] IR-induced injuries.…”
Section: Introductionmentioning
confidence: 99%
“…These results accord with our earlier findings on the liver 30) and gastric musosal tissue. 31) We found that MT is located predominantly in the Paneth cells at the base of the crypts of Lieberkühn in all the groups. Paneth cells play important roles in the elimination and storage of heavy metals and regulate the microbial flora of the intestine.…”
Section: Discussionmentioning
confidence: 64%
“…Other studies have reported that administration of vitamin E and glutamine reduced oxidative stress in the PHT gastric mucosa . In addition, zinc and zinc complex have also been reported to decrease gastric mucosal damage because of their anti‐oxidant effects . Furthermore, the zinc complex stimulates cell proliferation and attenuates the cytokine‐mediated oxidative damage to the gastric mucosa .…”
Section: Discussionmentioning
confidence: 97%
“…17,27 In addition, zinc and zinc complex have also been reported to decrease gastric mucosal damage because of their anti-oxidant effects. [28][29][30] Furthermore, the zinc complex stimulates cell proliferation and attenuates the cytokine-mediated oxidative damage to the gastric mucosa. 31 In the present study, we used DHLHZn as an anti-oxidant agent.…”
Section: Discussionmentioning
confidence: 99%